Anti-spasmodic action of crude methanolic extract and a new compound isolated from the aerial parts of Myrsine africana - Ahmad Bashir; Bashir Shumaila; Azam Sadiq (BMC, 2011)
Abstract Background Myrsine africana is an herbaceous plant that is traditionally used as appetizer and carminative. Locally, it is used for the treatment of pulmonary tuberculosis, rheumatism and diarrhea by healers. The aims of the current study were to screen the crude methanol extract obtained from the aerial parts (leaves and stem) of M. africana, for antispasmodic actions on isolated tissues and further to subject the ethyl acetate (EtOAc) fraction of plant to column chromatography for isolation of pure compounds. Methods The antispasmodic action of the crude methanol extract was measured on the spontaneous rabbit's jejunum preparations at concentration 0.01, 0.03, 0.1, 0.3, 1.0, 5.0 and 10.0 mg/ml. The crude extract was also applied, in similar concentrations, on KCl (80 mM) induced contractions to explain its possible mode of action. Results A new compound Myrsigenin was isolated from the EtOAc fraction of M. africana. The structure of the compound was identified with the help of 13C-NMR, 1H-NMR, HMBC, HMQC, NOESY and COSY. The plant crude methanol extract showed a significant antispasmodic action on rabbit jejunum and abolished the tissue contraction completely at concentration of 5.0 mg/ml. Conclusion The study concludes that the methanol crude extract of aerial parts of M. africana has antispasmodic action possibly through the calcium channel blocking mechanisms. A new compound Myrsigenin was isolated from the EtOAc fraction of the plant.